Students’ Ability In Solving Physics Problems on Newtons’ Law of Motion - Supeno, Supeno; Subiki, Subiki; Rohma, Laili Widya (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
The ability to solve physics problems is one of the goals in learning physics and a part of the current curriculum demands. One of the physics problems that are often the focus of attention in learning is Newton's law of motion. When solving physics problems on Newton's law of motion, students need to utilize various aspects of certain abilities and rules. The purpose of this study was to reveal how the students utilized aspects of the abilities and rules in problem-solving. The study was conducted by providing physics problems on Newton's law of motion to 105 high school students. The result showed that most students were able to write equations, solutions, and system of units correctly for each problem. However, students’ ability to determine the coordinate axes, depicts free-body diagrams, forces representation, and determine the resultant forces and direction of motion was unsatisfactory. Students tended to refer to the mathematical formulations in solving the problems. Therefore, physics learning that requires students to actively learn collaboratively, peer instruction, and procedural thinking can be used as an alternative learning strategy to overcome said problems.